Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1073/pnas.94.8.3554
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of function between mammalian and plant steroid 5α-reductases

Abstract: Arabidopsis det2 mutants are small darkgreen dwarfs displaying pleiotropic defects in light-regulated development during multiple stages of the plant life cycle. The DET2 gene encodes a protein that shares Ϸ40% sequence identity with mammalian steroid 5␣-reductases and is implicated in the synthesis of a class of plant steroids, the brassinosteroids. Here we show that the DET2 protein, when expressed in human embryonic kidney 293 cells, catalyzes the 5␣-reduction of several animal steroid substrates and has si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(85 citation statements)
references
References 38 publications
7
78
0
Order By: Relevance
“…Substrate Specificity of DET2-Previous in vitro assays demonstrated that DET2 catalyzes 5␣ reduction of 4-en-3-one to 3-one (7). In vivo feeding of labeled CR has also suggested a role for this enzyme in the conversion of 22-OH-4-en-3-one to 22-OH-3-one, a reaction in the early C-22 oxidation branch of BR biosynthesis (14).…”
Section: Cyp90a1/cpd Acts Upstream Of the C-5␣ Reductionmentioning
confidence: 99%
“…Substrate Specificity of DET2-Previous in vitro assays demonstrated that DET2 catalyzes 5␣ reduction of 4-en-3-one to 3-one (7). In vivo feeding of labeled CR has also suggested a role for this enzyme in the conversion of 22-OH-4-en-3-one to 22-OH-3-one, a reaction in the early C-22 oxidation branch of BR biosynthesis (14).…”
Section: Cyp90a1/cpd Acts Upstream Of the C-5␣ Reductionmentioning
confidence: 99%
“…To construct pMD1-gAtADF4, a genomic DNA fragment starting from 665 bp upstream of the AtADF4 start codon (e.g. ATG) to the stop codon TAA, was cloned into the binary vector pMD1 (Li et al, 1997), which was digested with HindIII and XbaI to remove 35S promoter. Primers 5#-GCGAAGCTTacatcttgtcttcacataatgaaaac-3# (forward) and 5#-GCGTCTAGAttaACCCATTTGTTGACCACCTGTCATTGAAGCCATgttgacgcggcttttcaaaacatcaagatcc-3# (reverse) were used to amplify this fragment.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…It is noteworthy that the human type 2 5a-reductase is also able to convert campesterol into campestanol and it is identified as ortholog of det2 in plant (Li et al 1997). The similarity between the two cases, LET-767/17b-HSD12 and det2/5a-reductase, suggests that LET-767 is involved in the biosynthesis of the active steroid in C. elegans that has a structure different from sex steroids in mammals but it could play an equivalent role.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to LET-767 that is able to metabolize vertebrate hormone androgen and estrogen, it has been shown that the plant enzyme responsive for det2 mutation, which causes small dark green dwarfs to display pleiotropic defects in lightregulated development during multiple stages of the Arabidopsis plant life cycle, is also able to convert vertebrate steroid hormone testosterone into dihydrotestosterone although its natural plant steroid hormone is campestanol, a brassinosteroid (Li et al 1997). It is noteworthy that the human type 2 5a-reductase is also able to convert campesterol into campestanol and it is identified as ortholog of det2 in plant (Li et al 1997).…”
Section: Discussionmentioning
confidence: 99%